PHRASEOLOGY IN MORPHOLOGY: IT’S A SIGN! - Beck, David (Linguistica Atlantica, 2019)
A well-studied property of the linguistic sign at the level of multi-word expressions is the capacity for these expressions to take on conventionalized and context-specific meanings, resulting in what are called phrasemes (Mel’čuk 1995). What is less well-studied is the existence of restricted expressions at the level of the word, what would be called morphological phrasemes. Consideration of restricted morphological ex-pressions reveals that these, on the whole, fall into the same types as multi-word phrasemes. This paper shows that this parallelism falls out directly from the nature of the morph as a linguistic sign and the susceptibility of linguistic signs at all levels of expression to the processes of phraseology. Recognizing this allows us to resolve a number of issues that have been used to argue against the morpheme as an analytical unit, and allows us to account for certain kinds of problematic constructions found in natural language.